On the Concurrence of Termination events in the Same Administrative Contract - García-Trevijano Garnica, Ernesto (2015)
The study addresses the way, according to the author, in which must be resolved the problem of the concurrence of termination events in an administrative contract. It is common that parties attribute non-compliances to each other or the coexistence of termination events with different effects each of them. In these situations, the termination event which must be applied as a matter of priority with its corresponding associated effects must be determined. In this context, it should be pointed out the doctrine of the Spanish Council of the State according to which the termination event occurred before in time is applicable as a priority. However, the author considers that should be taken into account the priority in time regarding the invocation of the termination event («activación») rather than its appearance («aparición»). Thus, the general rule is that termination events may be used by the party of the contract which has not caused them. However, the aforementioned rule does not entail that the party which may invoke a termination event, actually does so (la active), even though the presence of a material circumstance that justifies the existence of the termination event.On this basis, the author concludes that it is the priority in time of the invocation of the termination event [«activación»] (and not of its mere appearance) [y no de la simple «aparición»] which determines the termination event applicable as a priority when several termination events concur.